Medical 3D printing with a focus on Point-of-Care in Cranio- and Maxillofacial Surgery. A systematic review of literature - Ilirian Murtezani; Neha Sharma; Florian M. Thieringer (Annals of 3D Printed Medicine, 2022)
This systematic review aims to provide an overview of the published literature for three-dimensional printing (3DP) in cranio- and maxillofacial surgery applications utilizing either external laboratories (outsourced) or point-of-care (POC) fabrication facilities. Four digital databases (PubMed, Web of Science, Embase, and Cochrane Library) were systematically reviewed between January 2018 and December 2020. The review focused on the type of printed objects, the clinical indications, surgical outcome, time, cost, 3DP materials, and technologies used. Among the 2269 retrieved studies, 75 met the inclusion criteria. The studies that stated POC and outsourced production methods were 34.67% (n = 26) and 12% (n = 9). A large proportion of studies (54.67%, n = 41) did not specify the printing location. 3DP was used for surgeries of the entire craniomaxillofacial region, most specifically in mandibular reconstructions and orthognathic surgeries applications. Customized implants and osteosynthesis plates were exclusively printed in titanium using Powder Bed Fusion (PBF) 3DP technology. For surgical guides, models, and molds, Material Jetting, Material Extrusion, and Vat Photopolymerization, using either thermoplastic or photopolymeric resin materials were used. Medical 3DP is an assisting tool to plan, prepare, and even improve cranio- and maxillofacial surgery outcomes. With future technological advancement and research, 3DP has the potential to revolutionize cranio- and maxillofacial surgeries. With decreasing prices of three-dimensional (3D) printers and software packages, the disadvantage of the high acquisition and procurement costs for the hardware for in-house 3DP can be addressed and mitigated with time.